In search of immune cellular sources of abnormal cytokines in the blood in autism spectrum disorder: A systematic review of case-control studies - Nour-Eldine, Wared; Ltaief, Samia M.; Abdul Manaph, Nimshitha P.; Al-Shammari, Abeer R. (Frontiers in Immunology, 2022)
Abnormal cytokine levels in the circulating blood have been repeatedly reported in autism, however the underlying cause is still unclear. The aim of this systematic review is to investigate cytokine levels in peripheral blood compartments and identify their potential immune cellular sources in subjects with autism as compared to controls. We conducted an electronic database search (PubMed, Scopus, ProQuest Central, Ovid, SAGE Journals, and Wiley Online Library) from inception to 9th July 2020, and identified 75 relevant articles. Our qualitative data synthesis focused on results that were consistently described in at least three independent studies, and we reported results according to PRISMA protocol. We found cytokines IL-6, IL-17, TNF-a, and IL-1β increased in the serum, but not in plasma, in subjects with autism compared to controls, and we identified monocytes, neutrophils and CD4+ T cells as the potential sources of these elevated cytokines in autism. Cytokines IFN-γ, TGF-β, and RANTES were increased in the plasma of autism subjects compared to controls, and IFN-γ was likely produced by CD4+ T cells and natural killer (NK) cells, although conflicting evidence still exists for IFN-γ and TGF-β. Other cytokines IL-10, IL-5, and IL-4 were constantly unaltered in the plasma and in post-stimulated blood immune cells in autism individuals compared to controls. The frequency of T cells, monocytes, B cells and NK cells was unchanged in autism subjects compared to controls, suggesting that abnormal cytokines were unlikely due to altered cell numbers, and might be due to altered function of these cells in autism. Our results support existing reports of abnormal cytokines in autism and provide comprehensive evidence of potential cellular sources of these altered cytokines in the context of autism.